The Influence of Spindle Rotation Variation on The Wear of Carbide Cutting Tools Using a Gedee Weiler Lz-330 G Lathe - Aljufri, Aljufri; Syahputra, Rio Mandala; Alchalil; Putra, Reza; Setiawan, Adi; Rahman, Abdul; Suryadi (Malikussaleh Journal of Mechanical Science and Technology, 2025)
This study was conducted to determine the effect of spindle speed on the wear rate of CNMG 120404 carbide cutting tools using a dry machining process without coolant. The specimens used were AISI 1045 steel shafts, The cutting tool used was a CNMG 120404 carbide with conditions assumed to be the same in each experiment. The machine used was a Gedee Weiler LZ-330 G lathe with fixed parameters of 0.2 mm/revolution feed and 0.4 mm cutting depth, as well as spindle speed variations of 450 rpm and 660 rpm. The cutting time was carried out in stages starting from 5, 10, 15, 20, to 25 seconds. In this study, the parameters observed included tool wear and the surface roughness of the turning results on the AISI 1045 specimen. Tool wear was measured using visual macro documentation, while surface roughness was tested with a surface roughness tester. The results showed that the lowest wear value occurred at 450 rpm with a cutting time of 5 seconds, amounting to 0.012 mm, while the highest wear was achieved at 660 rpm with a cutting time of 25 seconds, amounting to 0.036 mm. In terms of surface quality, the lowest roughness value was obtained at 450 rpm with a cutting time of 5 seconds, amounting to 2.43 µm, while the highest roughness occurred at 660 rpm with a cutting time of 25 seconds, amounting to 4.56 µm. This data shows that the higher the speed and the longer the cutting time, the greater the tool wear and the lower the surface quality due to friction and increased temperature in the cutting zone. Wear on carbide tools is more influenced by friction between the tool and the workpiece and the duration of cutting. The speed factor is not as dominant as the effects of friction and cutting duration.